Age features of eyeball envelopes structure. - Ulyanova, N. A. (Морфологія / Morphologia / Morfologìâ, 2014)
Background. The absence of adequate experimental model of myopia is the actual problem in pathophysiological investigation of the myopia progression. Studies of the chick eye have formed the basis for several hypotheses of myopia development. The most pathogenically valid animal model of myopia is a deprivation model. Before introduction of this model in mammals, in particular rats, it is necessary to investigate the dynamics of age morphological changes in sclera and retina. Objective. To determine the age-related features of the sclera and retina in intact rats. Methods. The sclera and retina were investigated by optic microscopy method on the 14th, 21st, 30th, 40th, 50th, 60th, 70th, 90th days after birth. Results. It was determined that sagittal, vertical and horizontal sizes of rats eyes increase more intensively at the age period from the 14th to the 30th day. At this time the maximal number of fibroblasts was observed in sclera. The total amount of these cells decreases after 40 days of postnatal ontogenesis. At the same time changes in thickness and compactness of retina layers were detected. At the age period from the 14th to the 30th day definitive scleral tissue architecture is not yet formed, part of collagen fibrils are organized in bundles, part of them are loosely arranged. On the 90th day all collagen fibrils of scleral stroma and retina are arranged. Conclusion. The highest intensity of sclera and retina restructuring is observed between the 14th and 30th days of postnatal ontogenesis. This period could be considered as optimal for experimental modeling of myopia in rats.